NEW DATA ON UPPER KIMMERIDGIAN-TITHONIAN BIOSTRATIGRAPHY AND AMMONITES OF THE EASTERN CRIMEA - Arkad'ev V.V.; Rogov M.A. (My University, 2006)
Based on ammonites, Upper Kimmeridgian sediments are first established in the Crimean Mountains. The Kimmeridgian-Tithonian boundary recognizable in a continuous section is placed inside the Dvuyakomaya Formation of uniform largely clayey sediments. Assemblages of Kimmeridgian ammonites Lingulaticeras cf. procurvum (Ziegler), Pseudowaagenia gemmellariana Oloriz, Euvirgalithacoceras cf. tantalus (Herbich), Subplanites sp.) and Tithonian forms (?Lingulaticeras efimovi (Rogov), Phylloceras consaguineum Gemmellaro, Oloriziceras cf. schneidi Tavera, and Paraulacosphinctes cf. transitorius (Oppel) are described. A new biostratigraphic scheme proposed for the upper Tithonian-Berriasian of the Crimean Mountains includes the following new biostratigraphic units: the Euvirgalithacoceras cf. tantalus Beds of the upper Kimmeridgian, ?Lingulaticeras efimovi Beds of the lower Tithonian, and Oloriziceras cf. schneidi and Paraulacosphinctes cf. transitorius beds of the upper Tithonian. The middle Tithonian is proposed to consist of the fallauxi and semiforme (presumably) zones. The ammonities found determine the early Kimmeridgian-Berriasian age of the Dvuyakornaya Formation that is most likely in tectonic contact with the underlying Khutoran Formation. © MAIK "Nauka/Interperiodica" 2006.
Keywords: AMMONITES; CORRELATION; CRIMEAN MOUNTAINS; REGIONAL TECTONICS; TITHONIAN; UPPER KIMMERIDGIAN; ZONATION; Мезозой::Юрская::Верхний::Киммериджский; Мезозой::Юрская::Верхний::Титонский; Mesozoic::Jurassic::Upper::Kimmeridgian; Mesozoic::Jurassic::Upper::Tithonian